Phonetic detail and lateralization of reading‐related inner speech and of auditory and somatosensory feedback processing during overt reading. Issue 1 (13th September 2016) - Kell, Christian A.; Darquea, Maritza; Behrens, Marion; Cordani, Lorenzo; Keller, Christian; Fuchs, Susanne
Abstract: Phonetic detail and lateralization of inner speech during covert sentence reading as well as overt reading in 32 right‐handed healthy participants undergoing 3T fMRI were investigated. The number of voiceless and voiced consonants in the processed sentences was systematically varied. Participants listened to sentences, read them covertly, silently mouthed them while reading, and read them overtly. Condition comparisons allowed for the study of effects of externally versus self‐generated auditory input and of somatosensory feedback related to or independent of voicing. In every condition, increased voicing modulated bilateral voice‐selective regions in the superior temporal sulcus without any lateralization. The enhanced temporal modulation and/or higher spectral frequencies of sentences rich in voiceless consonants induced left‐lateralized activation of phonological regions in the posterior temporal lobe, regardless of condition. These results provide evidence that inner speech during reading codes detail as fine as consonant voicing. Our findings suggest that the fronto‐temporal internal loops underlying inner speech target different temporal regions. These regions differ in their sensitivity to inner or overt acoustic speech features. More slowly varying acoustic parameters are represented more anteriorly and bilaterally in the temporal lobe while quickly changing acoustic features are processed in more posterior left temporal cortices. Furthermore, processing of external auditory feedback during overt sentence reading was sensitive to consonant voicing only in the left superior temporal cortex. Voicing did not modulate left‐lateralized processing of somatosensory feedback during articulation or bilateral motor processing. This suggests voicing is primarily monitored in the auditory rather than in the somatosensory feedback channel. Hum Brain Mapp 38:493–508, 2017 . © 2016 Wiley Periodicals, Inc.